2017
DOI: 10.1016/j.strusafe.2016.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic physical modelling of corroded cast iron pipes for lifetime prediction

Abstract: Cast iron was the dominant material for buried pipes for water networks prior to the 1970s in Australia and overseas. At present, many water utilities still have a significant amount of ageing cast iron pipes. Cast iron is a brittle material and when large diameter cast iron pipes (diameters above 300mm) further deteriorate, the consequences of failure can be substantial. Focusing on the likelihood of failure to assist risk assessment, this paper examines the performance of large-diameter cast iron pipes using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(15 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Where wall loss is present the spread of the reduction is clearly evident and can be identified and measured. Such patches are modelled as ellipsoids (also depicted in Figure d overlaid over the reconstructed map), and their defining parameters can then be incorporated for stress calculation and remaining life prediction of the asset (Ji et al, ).…”
Section: Field Pipeline Inspection Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where wall loss is present the spread of the reduction is clearly evident and can be identified and measured. Such patches are modelled as ellipsoids (also depicted in Figure d overlaid over the reconstructed map), and their defining parameters can then be incorporated for stress calculation and remaining life prediction of the asset (Ji et al, ).…”
Section: Field Pipeline Inspection Resultsmentioning
confidence: 99%
“…Recent research in the space of stress analysis and failure prediction of critical CI water mains has revealed that over and above pit depths, as traditionally provided during condition assessment of a critical asset, there is a need to ascertain the presence and geometries of large corrosion patches in the pipe walls (Ji, Robert, Zhang, Zhang, & Kodikara, ; Kodikara, Valls Miro, & Melchers, ), such as those depicted in Figure d. There exist a wide range of NDT technologies developed for the purpose of material characterisation for CI (Liu & Kleiner, ), yet the provision to build dense 2.5D maps of remaining wall geometries for lined water mains has driven the need to design an internal inspection tool around PEC sensing technology, as a proven technique typically used in the NDT sector for ferromagnetic material thickness estimation (Huang, Xinjun, Zhiyuan, & Kang, ; Huang, Wu, Xu, & Kang, ; Xu, Wu, Li, & Kang, ), resilient to sensor lift‐off.…”
Section: Ndt Pipeline Wall Inspectionmentioning
confidence: 99%
“…In addition, as an extension of the deterministic analysis method adopted in this series of paper, the probabilistic physical modelling method presented in [29,30] has been proven to be a powerful tool for assessment of the lifetime risk of cast iron pipelines. It provides a new perspective to explore the long-term mechanical behavior and fragility of the pipeline in a statistical way and deserves further attention.…”
Section: Results Of Monte Carlo Simulationmentioning
confidence: 99%
“…With the proposed FEA approach, water utilities may be able to evaluate the remaining structural capacity of a corroded and aged CI pipe with more confidence. Additionally, the authors have developed an efficient statistically predictive model to approximate numerical solutions [24] and conducted probabilistic analysis based on FEA solutions [25]. Besides, a closed-form stress analysis solution close to numerical calculations of concentrated stresses due to corrosion is also being under developed.…”
Section: Discussionmentioning
confidence: 99%